Impact of sales promotion via broadcast message frequency, group information frequency and display picture frequency to the acceptance of promotion message - Yayuk Indriyani.S; Primada Qurrota Ayun, S.I.Kom, MA (Interaksi Online, 2016)
The activity of online bussiness by utilizing both social media and instant messenger was a trend in society. Wide range of products are on offer ranging from apparel, handbags, veils, food, home furnishings, and other service offerings. One of instant messenger that is often used to do this online business is the blackberry messenger (BBM). This application provides a variety of services that can be used as a medium for sales promotion including broadcast message, group, and display picture. This study aimed to determine the effect of sales promotion via broadcast message frequency, group information frequency, and display picture frequency promotional messages to an attitude of acceptance. The rational used in CMC theory (computer mediated communication) and S-O-R theory. This type of research is explanatory study. This study used a non-probability sampling technique was purposive sampling method in determining the sample of 40 respondents who met the criteria that 14-35 year-old audience that uses fuel applications, online sellers have contacts on BBM contacts, join a group of buying and selling in fuel and domicile anywhere. The data analysis used is multiple linear regressions with the help of SPSS. Based on the results of statistical calculations showed the signification of variables simultan is 0,018 where the results do show a value smaller than the 0.05 limit, which means that the sales promotion via broadcast message, group and display picture on blackberry messenger affect the acceptance of promotional messages.